Parametric Method-3 for the Geometry Optimization of Bis-coumarin - Tandon, H.C. (Asian Journal of Chemistry, 2010)
In the present work, the author described the, full geometry optimization of bis-coumarin extracted from Colvillea racemosa (Leguminosae).